Criteria for radiological evaluation of incorporation of stand-alone expandable cervical vertebral body replacement devices - Hassan Allouch; Sándor Kónya; Mootaz Shousha; Heinrich Boehm (International Journal of Spine Research - Peertechz Publications, 2020)
Introduction: Corpectomy is an important treatment option for various cervical pathologies and evaluation of treatment success on imaging can be even more difficult than for interbody fusion. Since for routine postoperative courses CT scanning seems not justified for evaluation of the fusion status this paper proposes markers for detailed evaluation of new on plain radiographs.  Methods: In a retrospective analysis of prospectively collected consecutive patients were included from whom a minimum 2 year clinical and radiological follow-up was available of stand-alone VBR after cervical corpectomy for degenerative stenosis. All patients received an expandable cage of rectangular shape. For assessment of bony incorporation of VBR devices we introduce the footprint sign in addition to McAfee´s sentinel sign. Three observers evaluated the lateral x-rays of the patients.  Results: 36 male and 33 female patients (mean age 61,9 years) underwent one-, two- or three-level anterior cervical corpectomy and fusion (29, 31 and 9 patients respectively). Radiological outcome was assessed at a mean follow-up of 44.5 months. Combined cranial and caudal footprint sign denoting fusion could be detected in 94% of the cases. A positive sentinel sign anterior or posterior was denoting fusion in 47 out of 68 evaluable cases. Four cases (5.9%) showed no sufficient anterior or posterior bridging after 2 years and were rated as pseudoarthrosis.  Conclusion: For routine patients with no or minor symptoms after cervical VBR the sentinel- and footprint-sign on standard x-rays is a good indicator of successful treatment. Once reached no additional (flex-ex or CT) diagnostics seems necessary.